Corneal cross-linking effects on ocular surface parameters and corneal topographic and optical characteristics in progressive keratoconus cases: a prospective single-arm study - Nazli Taheri; Afshin Lotfi Sadigh; Salar Abed Nikmanesh; Amir Tarkavani; Peyman Ghodraty; Amin Arasteh; Tahereh Attar Gharamaleki (BMC Ophthalmology)
Abstract Objective This study aims to evaluate the effects of epithelial-off corneal cross-linking (CXL) on the ocular surface and corneal topographic and optical parameters in progressive keratoconus (KCN) cases. Study design Prospective single-arm interventional study. Methods Thirty eyes of 25 progressive KCN cases needing corneal CXL entered the study. All the included eyes underwent an epi-off corneal CXl procedure following the Dresden protocol. The ocular surface parameters, including tear break-up time (TBUT), Schirmer I test, and Ocular surface disease index (OSDI), were evaluated at baseline, one and 6 months after the procedure. The corneal imaging with Pentacam (Oculus Inc.) was conducted at these visits, measuring topographic parameters (e.g., Kmax, K1, K2, and corneal thickness), indices (e.g., ISV, IVA, KI IHA), and aberrations. Results The median age of the patients was 24.0 (IQR:21.0–26.5) with a baseline BCVA of 0.045 LogMAR (IQR:0.000–0.301). The BCVA had no significant change in the last follow-up (p:1.000). The baseline median values for TBUT, Schirmer test, and OSDI were 11.0s, 13.0mm, and 28.12, demonstrating a significant ocular surface malfunction. These ocular surface parameters showed no significant change 6 months after CXL (p: 0.662, 0.534, and 0.372, respectively). The K1 and K2 values decreased significantly at the last follow-up compared to the baseline (44.4 vs. 45.6 (p:0.019) and 48.0 vs. 48.1 (p:0.008), respectively). The only topographic indices that improved 6 months after CXL was the index of surface variance (ISV) (70.50 vs. 61.70, p:0.036). The corneal front surface higher-order aberrations, including spherical aberration, coma, and trefoil, showed no significant change 6 months after CXL. Conclusion Progressive KCN cases cope with some ocular surface problems, such as dry eye, but the corneal CXL is safe for these cases without causing any deterioration in the ocular surface problems. The corneal CXL might not improve the topographic indices and corneal aberrations 6 months after the procedure. Graphical Abstract